Media Pembelajaran Budidaya Udang Vaname Berbasis Multimedia - Fitri Rizani (Jurnal Tika, 2023)
Learning Media is a very active media in this online world. This technology is an object introduction technique that is very widely used in the field of cultivation. In this case, learning media technology can be useful to assist the public in finding more complete and precise information about the science of vannamei shrimp farming. The learning media technology can be developed in the form of videos, photos and animations. In the field of video, learning media technology is still not too many users. Currently there are still many who use magazines and books as a means of reference where these means often make people disappointed with the results. The material obtained is only in the form of text and images. Therefore, researchers took the initiative to design learning media as an educational and interesting tool. This promotional media is created using the Adobe Flash application.